2006
DOI: 10.1002/mds.21170
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations in Wilson's disease: Report of 119 cases

Abstract: We describe the neurological manifestations of 119 patients with WD (93 index cases and 26 affected family members) seen between 1963 and 2004. The mean age at symptoms onset was 19.6 years (range, 7-37 years). Medical records were reviewed for the patient's first neurological examination. The most frequent neurological manifestations observed were dysarthria (91%), gait disturbance (75%), risus sardonicus (72%), dystonia (69%), rigidity (66%), tremor (60%), and dysphagia (50%). Less frequent manifestations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
201
3
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(221 citation statements)
references
References 19 publications
11
201
3
6
Order By: Relevance
“…In this study, children with disease onset\8 years of age were mostly boys, which may be explained by the cultural philosophy of better care for boys. Mean age of appearance of neurological symptoms did not differ from that of hepatic symptoms (9.8 compared with 10.9 years); furthermore, onset of neurological symptoms was much earlier than that reported in the literature (Machado et al 2006). Genotype-phenotype correlation analysis was limited in this study due to diversity of the mutations detected, but it was found that frameshift and nonsense mutations (a possible predictor of severe phenotype) were found in 50% of children with age of onset \8 years compared with only 26% of patients with age of onset [10 years.…”
Section: Discussioncontrasting
confidence: 53%
“…In this study, children with disease onset\8 years of age were mostly boys, which may be explained by the cultural philosophy of better care for boys. Mean age of appearance of neurological symptoms did not differ from that of hepatic symptoms (9.8 compared with 10.9 years); furthermore, onset of neurological symptoms was much earlier than that reported in the literature (Machado et al 2006). Genotype-phenotype correlation analysis was limited in this study due to diversity of the mutations detected, but it was found that frameshift and nonsense mutations (a possible predictor of severe phenotype) were found in 50% of children with age of onset \8 years compared with only 26% of patients with age of onset [10 years.…”
Section: Discussioncontrasting
confidence: 53%
“…This line of investigation is up to nowadays one of the most traditional of the Neurologic Clinic (HC-FMUSP) and for the last 20 years, has counted with an effective participation of researchers from the Gastroenterology department [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Wilson's disease (WD) is a rare autosomal recessive metabolic disease resulting from mutations in the ATP7B gene, which has been mapped to chromosome 13q14 1,2 . The ATP7B gene encodes a copper-transporting adenosine triphosphatase (ATPase) protein, which is expressed most abundantly in the liver and is responsible for biliary copper excretion.…”
mentioning
confidence: 99%
“…The ATP7B gene encodes a copper-transporting adenosine triphosphatase (ATPase) protein, which is expressed most abundantly in the liver and is responsible for biliary copper excretion. Because of defects in this gene, copper accumulates in several organs, especially the liver, brain (basal ganglia) and corneas 1,2 . Clinically, patients present with predominantly hepatic, psychiatric and neurological symptoms, particularly dystonia, tremor and parkinsonism.…”
mentioning
confidence: 99%